Prospects for dedicated energy crop production and attitudes towards agricultural straw use: the case of livestock farmers - Wilson, P.; Glithero, N.J.; Ramsden, Stephen J. (Elsevier, 2014)
Second generation biofuels utilising agricultural by-products (e.g. straw), or dedicated energy crops (DECs) produced on ‘marginal’ land, have been called for. A structured telephone survey of 263 livestock farmers, predominantly located in the west or ‘marginal’ upland areas of England captured data on attitudes towards straw use and DECs. Combined with farm physical and business data, the survey results show that 7.2% and 6.3% of farmers would respectively consider growing SRC and miscanthus, producing respective maximum potential English crop areas of 54,603 ha and 43,859 ha. If higher market prices for straw occurred, most livestock farmers would continue to buy straw. Reasons for not being willing to consider growing DECs include concerns over land quality, committing land for a long time period, lack of appropriate machinery, profitability, and time to financial return; a range of moral, land quality, production conflict and lack of crop knowledge factors were also cited. Results demonstrate limited potential for the production of DECs on livestock farms in England. Changes in policy support to address farmer concerns with respect to DECs will be required to incentivise farmers to increase energy crop production. Policy support for DEC production must be cognisant of farm-level economic, tenancy and personal objectives.